Kajian Teori dan Pandangan Alkitab Mengenai Kepemimpinan Visioner (Jurnal Pendidikan Agama dan Teologi, 2025)
This article examines theoretically about visionary leadership starting from the definition, benefits, weaknesses, and biblical views on visionary leadership. This research uses a library research approach. Visionary leaders are able to formulate a vision of the future, inspire commitment, and lead innovative change. The benefits include encouraging innovation and adaptive culture, but there is a risk of dependence and lack of attention to short-term needs. From a Christian perspective, visionary leadership stems from a relationship with God, where vision is divine revelation manifested through prayer and obedience. Biblical figures such as Nehemiah, Joshua, and Moses are examples of visionary leaders who combine faith and strategy. In conclusion, effective visionary leadership must balance strategic and spiritual vision for the success of the organization and community.